Kumkoy - Igneada from the Coastline and Territorial Waters Near Diffraction Effects on the Environment and Relief of Planning Criteria - (:unkn) unknown (MARMARA UNIV, 2015)
This study is located between the coastal Igneada Kumkoy and physical potential of its surroundings and has been shaped over its role in the planning and development of this potential. This study is a summary of the Master's Thesis that was created with the same name. The study determined the location of the survey area before creating is then determined physical potential in this area. Physical preparation for potential relief, climate, soil, vegetation, and hydrography were considered as factors. After the physical potential of the targets set out in the direction that will shape the construction and development of these properties and these goals are to be followed around by an emphasis on work completed.
Keywords: Igneada; Kumkoy; structural; relief; planning